Primary interphase dendritic growth via unsteady-state horizontal solidification of an Al-Cu-Nb alloy - Hoffmann, Evaldo da Cruz; Feio, Bruno Yuji Goto; Dillon, Thiago Maués Oliveira; Azevedo, Hugo André Magalhães de; Rocha, Fernando Sousa da; Rocha, Otávio Fernandes Lima da (Seven Editora, 2023)
Aluminum and its alloys, compared to steel, have a higher strength/weight ratio, good electrical and thermal conductivity, and better corrosion resistance. Among the various aluminum alloys registered today, we can highlight those that make use of copper, the third most consumed metal in the world. In this context, niobium stands out, which plays an important role in the production of metallic alloys due to its high melting point, resistance to acid attack, and superconductivity at high temperatures. In recent decades, several studies have been carried out to establish the relationship between the thermal solidification parameters and typical as-cast structure in macrostructural and microstructural scales in aluminum alloys, aiming to optimize the properties of these alloys. In this sense, the main objective of this work was to investigate the effects of heat flow parameters, such as growth and cooling rates (VL and TR), on primary interphase dendritic growth (1α) in equiaxed dendrites in Al-3Cu-0.5Nb (wt.%) alloy (wt.%), which was horizontally solidified in a recent study. The 1α variation with VL and TR has been characterized by mathematical equations given by the general expressions 1α=Constant. (VL)-1.1 and 1α=Constant.(TR)-0.55, which represents the interphase dendritic growth laws, where the exponents -0.55 and -1.1 are in absolute agreement with the primary spacing growth laws in columnar dendrites. DOI:https://doi.org/10.56238/alookdevelopv1-173